2014
DOI: 10.1080/00438243.2014.953711
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the complexity of domestication: a response to Rowley-Conwy and Zeder

Abstract: In their critique of our paper (Krause-Kyora et al. 2013), Rowley-Conwy and Zeder focus on two primary issues. Firstly, they discuss issues associated with the terminology and definitions of animal domestication. Secondly, they question the techniques we employed to explore it. While we completely agree with their points related to terminology, we feel they have misunderstood both the principals and application of shape analyses using geometric morphometrics, and that this misunderstanding undermines their cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This disadvantage has, for instance, been recently argued as a support for the claim that Mesolithic hunters-gatherer populations in Northern Europe possessed domestic pigs acquired from near-by farming communities (Zeder 2012;Krause-Kyora et al 2013;Evin et al 2014;Rowley-Conwy and Zeder 2014). Otherwise, our results suggest that the benefits of introgression between managed and free-living populations are not a one way street: good when going from free-living to managed, but bad the other way around.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This disadvantage has, for instance, been recently argued as a support for the claim that Mesolithic hunters-gatherer populations in Northern Europe possessed domestic pigs acquired from near-by farming communities (Zeder 2012;Krause-Kyora et al 2013;Evin et al 2014;Rowley-Conwy and Zeder 2014). Otherwise, our results suggest that the benefits of introgression between managed and free-living populations are not a one way street: good when going from free-living to managed, but bad the other way around.…”
Section: Discussionsupporting
confidence: 64%
“…; Evin et al. ; Rowley‐Conwy and Zeder ). Otherwise, our results suggest that the benefits of introgression between managed and free‐living populations are not a one way street: good when going from free‐living to managed, but bad the other way around.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of the domestication literature, however, demonstrated that far from being unusual, introgression between indigenous wild populations and translocated domestic populations domesticated elsewhere is common in both plants and animals (110). This admixture often results in an imported domestic population taking on the genetic [and morphological (111)] appearance of the local wild population, leading researchers to the false conclusion that the local wild population gave rise to the domestic one through an independent domestication process. In fact, this process is so pervasive that Larson & Fuller (79) have suggested the word domestication be reserved only for the independent process (regardless of pathway), and they introduce the term "introgressive capture" to refer to subsequent admixture between introduced domestic populations and local wild populations that were never domesticated.…”
Section: Wwwannualreviewsorg • Evolution Of Suidae 313mentioning
confidence: 99%
“…This is not to say that evidence of genetic or resulting phenotypic change necessarily takes priority over other markers. The detection of "domestication" genes controlling coat color among pigs recovered from forager settlements in northern Europe, for example, does not indicate that these hunter-gatherers "possessed" domestic pigs or that these were "the earliest domestic animals" in this region (57,77). Rather, it indicates that these pigs had some degree of domestic ancestry, likely acquired through introgression between escaped domestic pigs from nearby farming communities and indigenous wild boar (60,78).…”
Section: Impacts and Markersmentioning
confidence: 99%